2017
DOI: 10.3390/ijms18102083
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 Is Involved in the Metallothionein-Mediated Rice Tolerance to Copper and Cadmium Toxicity

Abstract: Cadmium (Cd) and excess copper (Cu) are toxic to plants, causing a wide range of deleterious effects including the formation of reactive oxygen species. Metallothioneins (MTs) may protect plant cells from heavy metal toxicity by chelating heavy metals via cysteine thiol groups. They may also function as antioxidants. The study investigated the relationship of H 2 O 2 production and ricMT expression in rice radicles and rice suspension cells under Cu or Cd stress. The results showed that H 2 O 2 production in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(11 citation statements)
references
References 46 publications
1
10
0
Order By: Relevance
“…Transgenic plants accumulate more Cd 2+ in root when compared to the wild type, suggest that ZjMT may have a function in Cd 2+ retention in roots and, therefore, decrease the toxicity of Cd 2+ . Consistent with our results, heterologous expression of ricMT in transgenic rice (Zhang et al, 2017) and OsMT2c in transgenic Arabidopsis (Liu et al, 2015) provided increased tolerance against Cd stress.…”
Section: Discussionsupporting
confidence: 91%
“…Transgenic plants accumulate more Cd 2+ in root when compared to the wild type, suggest that ZjMT may have a function in Cd 2+ retention in roots and, therefore, decrease the toxicity of Cd 2+ . Consistent with our results, heterologous expression of ricMT in transgenic rice (Zhang et al, 2017) and OsMT2c in transgenic Arabidopsis (Liu et al, 2015) provided increased tolerance against Cd stress.…”
Section: Discussionsupporting
confidence: 91%
“…Functional yeast analysis of the cDNA library was undertaken, which resulted in the identification of several genes (including the date palm PdMT2A gene) that could play a critical role in salinity tolerance in date palm [18]. MTs are well known for detoxification of heavy metal homeostasis [28,42,43]. However, MTs have also been shown to play a role in drought and salinity tolerance [33,44].…”
Section: Discussionmentioning
confidence: 99%
“…CUP1 in S. cerevisiae and LbMT1 and LbMT2 from Laccaria bicolor were all identified as having a key role in maintaining the local redox balance by preventing the Fenton reaction and scavenging ROS. Zhang et al found that the overexpression of ricMT blocked H 2 O 2 accumulation and significantly increased the survival rate of rice cells stressed by Cu and Cd. DPPH free radicals were found to be cleared by yeast MTs in vitro in the concentration range of 20–100 μg·mL −1 .…”
Section: Discussionmentioning
confidence: 99%